Service Quality of Museums for Sustainable Tourism: An Empirical Study of Museums in Bangladesh: An Empirical Study of Museums in Bangladesh - Sharmin, Dilruba; Haque, Farina (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
Museums are the major cultural resources of a country that emphasize tourism and economic growth. For this, the service quality is important, and should be measured by systematic methods and analysis on a yearly basis. In Bangladesh, due to the lack of knowledge, these cultural resources are not properly utilized and managed, which affects the conservation and preservation of our historical resources as well as national development. This study aims to understand the quality of service of museums in Bangladesh. It helps us understand the concepts prominent among visitors engaging in museum experiences and the barriers for museums to provide a better quality of service to their visitors. The study was conducted on 16 renowned museums across three divisions of Bangladesh: Dhaka, Rajshahi, and Chattogram. Field visits and in-depth interviews are applied as a methodology for data collection. The study suggests that most of the known Bangladeshi museums need help in providing a better quality of service for their visitors due to inadequate and unplanned infrastructure, exhibition style, service provided, and supportive attitude. This article aims to create a service quality measurement database for museums, enhancing their service quality and promoting sustainable tourism. The increased visitor numbers will boost local communities' income, contribute to the country's Sustainable Development goal 8, and protect local culture. JASBH, Vol. 69(2), 2024, pp. 259-280